2017
DOI: 10.1136/gutjnl-2017-314454
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies inversion in the CTRB1-CTRB2 locus to modify risk for alcoholic and non-alcoholic chronic pancreatitis

Abstract: ObjectiveAlcohol-related pancreatitis is associated with a disproportionately large number of hospitalisations among GI disorders. Despite its clinical importance, genetic susceptibility to alcoholic chronic pancreatitis (CP) is poorly characterised. To identify risk genes for alcoholic CP and to evaluate their relevance in non-alcoholic CP, we performed a genome-wide association study and functional characterisation of a new pancreatitis locus.Design1959 European alcoholic CP patients and population-based con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 31 publications
3
90
0
4
Order By: Relevance
“…The aforementioned new discovery was made from the analysis of European subjects 1. Herein, we attempted to confirm this discovery in a cohort of Chinese patients with idiopathic chronic pancreatitis (ICP).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The aforementioned new discovery was made from the analysis of European subjects 1. Herein, we attempted to confirm this discovery in a cohort of Chinese patients with idiopathic chronic pancreatitis (ICP).…”
mentioning
confidence: 91%
“…Finally, they provided in vitro evidence that CTRB1 was less efficient in degrading anionic trypsinogen (PRSS2) than CTRB2 (note that rapid degradation of PRSS2 conferred by a PRSS2 missense variant protects against CP) 3. Taking together, Rosendahl and colleagues concluded that the major inversion allele increases the risk of pancreatitis by negatively affecting protective trypsinogen degradation 1. Indeed, this new finding further strengthens the pivotal role of the trypsin-dependent pathway in the aetiology of CP 4 5…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…A few genome-wide association studies have been performed to date, mainly in chronic pancreatitis and recurrent acute pancreatitis patients. Studies by Whitcomb et al [55] and Rosendahl et al [65] were able to identify new susceptibility loci in the claudin-2 gene ( CLDN2 ), as well as a gene conversion event in the chymotrypsin B CTRB1–2 locus, which modifies the risk for alcoholic and nonalcoholic chronic pancreatitis [65]. …”
Section: Recurrent Acute and Chronic Pancreatitis: Distinction And Etmentioning
confidence: 99%
“…Genetic causes are less frequent and include mutations in cationic trypsinogen 1 and 2 (PRSS1/2), serine protease inhibitor Kazal-type 1 (SPINK1), cystic fibrosis transmembrane conductance regulator (CFTR), chymotrypsin C (CTRC), carboxypeptidase A1 (CPA1), carboxyl ester lipase (CEL), and calcium-sensing receptor (CASR) [14-16]. In their pangenetic association study, Rosendahl et al [17] identified a variety of other genetic loci that alter susceptibility to CP, supporting the concept of multiple factors engaging in promoting the disease with a clinically almost stochastically appearing risk. Rare causes include primary hyperparathyroidism as well as posttraumatic states.…”
Section: Definition Epidemiology Causes and Manifestationmentioning
confidence: 99%